PENGARUH PEER TEACHING MODEL TERHADAP PEMBELAJARAN PERMAINAN BOLA VOLI PASSING BAWAH DI KELAS XI SMA NEGERI 1 TEGALWARU KARAWANG - Desta Mayang Arum; Tedy Purbangkara; Siswanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this thesis is to determine the effect of peer teaching model on volleyball learning for class XI at SMA Negeri 1 Tegalwaru Karawang. To answer the research problem formulation that has been formulated, the author uses a quantitative approach with an experimental method. This research was conducted at SMA Negeri 1 Tegalwaru Karawang by taking one class as a research sample, namely class XI, which totaled 36 respondents from 180 class XI students. The sampling technique used in this study was purposive sampling. The form of the research design used a pre-experimental design with a one-group pretest-posttest design. The research instrument used a basic technique test instrument for underhand passing movements, from this study the average before treatment and after treatment experienced a significant increase, namely underhand passing increased from a pretest mean of 54.67 to a posttest mean of 77.08. Meanwhile, the results of the calculation of the Paired Sample T Test hypothesis test with the data obtained from this study are a significance value (2-tailed) of 0.000 < 0.05, meaning that there is a significant influence between the average value before treatment and the average value after treatment. It can be concluded that the peer teaching model can influence volleyball learning for class XI at SMA Negeri 1 Tegalwaru Karawang.